Global positioning system analysis of running performance in female field sports: A review of the literature. - Hodun, M.; Clarke, R.; De Ste Croix, M. B. A.; Hughes, J. D. (Strength and Conditioning Journal, 2016)
The use of global positioning systems (gps) in analyzing field sport performance is a recent development, particularly in soccer, rugby, and field hockey. Research with gps in female field sports has centered on match performance, fatigue, and training intensity. Of particular concern for gps analysis is the need for standardized methods to determine the occurrence of high-intensity running and sprinting. Gps analysis for female field sport athletes can assist in development of training plans and monitoring protocols in field sports. The aim of this article is to review the published studies to provide useful information to inform coaches' s&c programming.